2005
DOI: 10.1029/2005wr004222
|View full text |Cite
|
Sign up to set email alerts
|

Effective discharge analysis of ecological processes in streams

Abstract: [1] Discharge is a master variable that controls many processes in stream ecosystems. However, there is uncertainty of which discharges are most important for driving particular ecological processes and thus how flow regime may influence entire stream ecosystems. Here the analytical method of effective discharge from fluvial geomorphology is used to analyze the interaction between frequency and magnitude of discharge events that drive organic matter transport, algal growth, nutrient retention, macroinvertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 42 publications
3
139
0
1
Order By: Relevance
“…Predicted plant and habitat response can then be used to support species or community habitat suitability models (USFWS, 1980). Dynamic physical forces are well known ecological drivers in large rivers (Doyle et al 2005). Methods and data presented here can help estimate physical-ecological cascades resulting from hydrologic and geomorphic alteration of large rivers.…”
Section: Hydro-geomorphic Classification and Potential Vegetation Mapmentioning
confidence: 99%
“…Predicted plant and habitat response can then be used to support species or community habitat suitability models (USFWS, 1980). Dynamic physical forces are well known ecological drivers in large rivers (Doyle et al 2005). Methods and data presented here can help estimate physical-ecological cascades resulting from hydrologic and geomorphic alteration of large rivers.…”
Section: Hydro-geomorphic Classification and Potential Vegetation Mapmentioning
confidence: 99%
“…4.10), may affect biota independently or in association with flow alteration. Poff and Zimmerman (2010) mentioned that there are no studies reported that focus primarily on ecosystem functional responses (e.g., riparian production, nutrient retention), even though many ecological processes are clearly flow dependent (Hart and Finelli 1999;Doyle et al 2005, cited in Poff and Zimmerman 2010). They emphasized that this absence points to an obvious research gap in the environmental flows research.…”
Section: Ecological Responses To Altered Flow Regimementioning
confidence: 99%
“…Biedenharn et al (1999) provide a thorough review of effective discharge calculation. Doyle et al (2005) proposed effectiveness analysis as a technique for assessing critical thresholds in ecological response to river discharge. They demonstrated the applicability of effectiveness analysis using geographically dispersed, available data sets for five ecological processes: organic matter transport, algal growth, flood transport of macroinvertebrates, nutrient transport and retention, and physical habitat availability.…”
Section: Primary Stream Functions Example Application Benefitting Fromentioning
confidence: 99%